2018
DOI: 10.1111/1442-1984.12204
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive ecology of three rareNorthAmericanPinguiculaspecies

Abstract: Pinguicula (Lentibulariaceae) is a genus of more than 100 carnivorous plant species. A handful of comprehensive studies have examined the reproductive ecology of these species, mostly in Europe and none in the USA. During 2013–2016 different aspects of the reproductive ecology of P. ionantha, P. lutea and P. planifolia were studied at multiple locations in the Florida Panhandle, USA. All three species are of conservation concern within the study region and some aspects of their reproductive ecology may be cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In July 2017, 50 plants bearing floral buds were marked in the Cuernavaca population and randomly assigned to five hand-pollination treatments (n = 10 per treatment). This sample size was previously used in earlier studies to characterize the pollination system of P. moranensis (Villegas & Alcalá, 2017) and other Pinguicula species (Molano-Flores et al, 2018). The treatments performed within the recipient population were: self-fertilization (0 m) and crosses performed at four distances (1, 4, 460 and 9,900 m).…”
Section: Experimental Designmentioning
confidence: 99%
See 4 more Smart Citations
“…In July 2017, 50 plants bearing floral buds were marked in the Cuernavaca population and randomly assigned to five hand-pollination treatments (n = 10 per treatment). This sample size was previously used in earlier studies to characterize the pollination system of P. moranensis (Villegas & Alcalá, 2017) and other Pinguicula species (Molano-Flores et al, 2018). The treatments performed within the recipient population were: self-fertilization (0 m) and crosses performed at four distances (1, 4, 460 and 9,900 m).…”
Section: Experimental Designmentioning
confidence: 99%
“…Thus, the fitness of carnivorous species could depend on interactions with both prey and pollinators (Jürgens, Sciligo, Witt, El-Sayed, & Suckling, 2012). Carnivorous plants display wide diversity of reproductive systems, and studies addressing reproductive ecology have documented variation in flower structure and histochemistry, flower phenology and longevity, mating system, pollination syndrome, and visitation rate, among others (Adam, 1998;Chua, 2000;Clivati, Cordeiro, Płachno, & Miranda, 2014;Hobbhahn, Küchmeister, & Porembski, 2006;Kato, 1993;Lowrie, 2001;Meindl & Mesler, 2011;Molano-Flores et al, 2018;Molau, 1993;Murza & Davis, 2003;Ne´eman et al, 2006;Olivencia, Claver, & Alcaraz, 1995;Płachno et al, 2018;Renner, 1989;Schnell, 1983;Villegas & Alcalá, 2017). These studies have identified selfing and outbreeding species, but the information on the effects of varying distance to pollen donors is scarce in carnivorous plant species.…”
mentioning
confidence: 99%
See 3 more Smart Citations